Patterns of alcohol consumption in university students: a European study. (30th September 2020) - Ladner, J; Brumboiu, I; Ciobanu, E; Lukács, A; Croitoru, C; Tavolacci, M P
Abstract: Background: In Europe, alcohol consumption (AC), especially binge drinking (BD) and behavioural risk factors among students in higher education remain to be investigated. The aim of the study was to assess the evolution of AC, and BD and the behavioural factors associated in university students in four European universities: Chisinau (Ch) in Republic of Moldova, Cluj-Napoca (Cl) in Romania, Miskolc (Ms) in Hungary and Rouen (Ro) in France. Methods: In the four countries in 2018, students in higher education completed an anonymous standardized self-questionnaire. The questionnaire collected age, gender (M, W), housing, curricula, smoking, cannabis consumption. Alcohol abuse problems were assessed by ADOSPA test and by AUDIT test.. Frequent BD was determined as a consumption of five or most alcoholic drinks on one occasion at least twice a month. A risk profile of consumers was conducted according to the consumption of alcohol and frequency of BD. Results: A total of 3076 students were included, 705 in Ch, 582 in Cl, 534 in Ms and 1255 in Ro. Globally, the sex-ratio was quite similar (M:F=0.45), the mean age was 21.2 (SD = 4.1). In Ro, 83.6% of students consumed alcohol at least 1 per week, 86.4% in Ch, 27.6% in Cl, 43.6% in Ms. The prevalence of frequent BD was 15.9% in Ms and 13.8% in Ro, 11.5% in Ch and 12.6% in Cl. Alcohol hazardous drinking and risk of addiction levels were found in 19.3% of students in Ro, 27.6%, in Ms, 7.4% in Cl and 13, 6% in Ch. Regarding patterns of consumption significant difference by gender were found. After multivariate analysis, different risk behaviours were found. Conclusions: BD patterns in students were quite similar in the four countries, especially in male students. BD appears as a frequent, whose consequences remain to be investigated. It might be necessary in the future to screen students for potential ED upon entry to the university and also to inform student about the risk of ED and advise them to consult a healthcare professional. Key messages: The study showed that alcohol is a central part of students' lives in France, Hungary, Republic of Moldova and Romania. Specific target populations for public health interventions were identified.